Click mechanism for 22-cm span flapping wings - Tan, Adam Boon Hao (2016)
Flapping wing flight offers many potential applications for micro air vehicles (MAV) that requires high agility to manoeuvre through narrow spaces. However, flapping wing flight requires large amounts of energy to move the wings. Insects are found to possess energy-storing thoracic mechanisms, which has inspired man to recreate the energy-storing mechanism with the use of compliant hinges for flapping wing micro air vehicles (FWMAVs). One such mechanism is the Dipteran inspired “click” mechanism. A small wingspan “click” mechanism prototype was previously developed by Yao Wei Chin, but this prototype did not produce sufficient thrust to lift off. This final year project aims to develop a large wingspan prototype FWMAV which utilises the “click” mechanism. A working prototype was successfully developed and tested. Wing kinematics, thrust and power input are recorded and analysed. The thrust output, although greater than the previous prototype, is still not sufficient for lift off. However, this prototype shows good potential for future development.